Arabic Sign Language Adaptation In Teaching Fardhu Ain To The Disabled Hearing - Mohd Rashid, Syar Meeze; Mohd Yasin, Mohd Hanafi; Ashaari, Noraidah Sahari (IJIE (Indonesian Journal of Informatics Education), 2018)
The purpose of this study is to review the consensus of experts in the adaptation of the use of sign language in teaching fardhu ain to the disabled hearing. This study has used the technique of fuzzy delphi to seek a consensus of experts skilled in sign language to answer the review questions. Distributed instruments includes 14 items in order to obtain a consensus of experts. The findings show that there are five items that need to be adopted in the Arabic sign language that is the sign language related to the pronouncement of the Shahadah, beliefs and tenets of islam, body cleanliness, the aurat  and prayer with the deffuzification value of 0.767.